The intersection of public administration and criminal justice: administrative criminology in action - Adhraa Oudha Hussen Al-Saedi; Ayat Mothafer Al-Turath; Ahmed Taher Kadhim; Dmytro Khlaponin (Encuentros)
The relationship between public administration and criminal justice is intricate and has a profound impact on the governance of society, particularly in the domains of policy-making, resource allocation, and interagency cooperation. The objective of this research is to examine the capacity of this approach to enhance policy formulation, improve the distribution of resources, and foster more cooperation across different organizations, eventually resulting in more effective governance and administration of justice.This study uses qualitative analysis to examine the implementation of Administrative Criminology concepts in various circumstances. It assesses the outcomes and repercussions of these efforts. The method involves doing a comprehensive analysis of current research and case studies to identify the benefits and limitations of integrating Administrative Criminology into both public administration and criminal justice operations. The research demonstrates that Administrative Criminology offers valuable perspectives for resolving the challenges that emerge from the intersection of public administration and criminal justice. Efficiently applying its principles leads to enhanced policy execution, optimized resource management, and enhanced interagency cooperation. However, the study also acknowledges the potential drawbacks, such as the complexities of coordinating across different departments and the risks of oversimplification.